Work-Life Balance among Married Women Working in Public Sector (Journal of Governance and Development (JGD), 2023)
This study is to determine whether married women working in the publicsector are able to sustain work-life balance and to elicit their views andsuggestions on the support system needed to improve their work-life balance.This study adopts a quantitative method. Surveys were used as the main toolto gather data from seventy-six (76) women working in various public sectorsin Komplek Tun Abdul Razak (KOMTAR) Penang. The study discovers that ingeneral, married women working in public sectors are able to sustain worklifebalance. The main support is the spouses who often help the women withtheir housework. However, most of the housework is done during weekendsbecause of the limited time during the working days. The respondents agreethat they are also able to spend good quality time with their families. Thesupport system suggested by the respondents to promote work-life balanceincludes leave policies, flexible working hours, childcare centers and nurseryroom facilities at workplaces. Services suggested are Employee AssistanceProgram (EAP), counseling services and series of trainings for public sectoremployees in providing skills and knowledge to improve work-life balance.